Cancer screening rate in people with diabetes in the Korean population: results from the Korea National Health and Nutrition Examination Survey 2007-2009 - Chuck, Kumban Walter (Epidemiol Health, 2017)
OBJECTIVES: To investigate the screening rates for gastric, breast, and cervical cancer in people with diabetes compared with people without diabetes. METHODS: Data from the Korea National Health and Nutrition Examination Survey (2007-2009) were used. Cancer-free men who were 40 years old and over and cancer-free women who were 30 years old and over were included. The lifetime screening rate and regular screening rate were compared in people with and without diabetes. RESULTS: Fewer people with diabetes than people without diabetes had ever received cancer screening (53.5 vs. 59.5%, p<0.001 for gastric cancer; 60.5 vs. 71.5%, p<0.001 for breast cancer; and 49.1 vs. 59.6%, p<0.001 for cervical cancer). Fewer people with diabetes than people without diabetes received the recommended screenings for gastric cancer (38.9 vs. 42.9%, p<0.001), breast cancer (38.8 vs. 44.6%, p<0.001), and cervical cancer (35.1 vs. 51.2%, p<0.001). In subgroup analyses according to socioeconomic factors, the lifetime and recommended screening rates were lower in the diabetic population in most socioeconomic subgroups. In the multivariate analysis adjusted for socioeconomic factors, people with diabetes showed lower lifetime screening rates for gastric and cervical cancer (odds ratio [OR], 0.8; 95% confidence interval [CI], 0.7 to 0.9 and OR, 0.7; 95% CI, 0.6 to 0.9), and lower regular screening rates for breast and cervical cancer (OR, 0.7; 95% CI, 0.6 to 0.9 and OR, 0.7; 95% CI, 0.5 to 0.9). CONCLUSIONS: The cancer screening rate in people with diabetes was lower than in people without diabetes. Considering the higher cancer risk in people with diabetes, efforts to increase the screening rate in this high-risk population should be implemented.